Pedagogical moves and student thinking in technology‐mediated medical problem‐based learning: Supporting novice‐expert shift. (22nd July 2019) - Reilly, Colby M.; Kang, Stephanie Y.; Grotzer, Tina A.; Joyal, Julie A.; Oriol, Nancy E.
Abstract: Technology‐mediated simulation is often used in medical problem‐based learning (PBL) approaches to offer authentic contexts and immersive engagement for learning. However, critiques argue that these approaches are lacking in the structure necessary to support productive learning—that they often result in mindless doing without the thinking processes needed that lead to deeper understanding and expertise. This paper presents data from a technology‐mediated simulation, called HMS MEDscience, to demonstrate: (1) that it effectively leads to greater expert reasoning—evident through responses in content knowledge and problem‐solving ability that more closely aligned with a rubric of expert responses to the same questions; (2) through a series of case studies, the implicit pedagogical moves the teachers make to support students' thinking processes. Significant pre‐ to posttest gains indicate more expert reasoning. In addition, classroom videos indicate shifts from novice toward more expert medical science reasoning and illustrate the fine‐grained supporting moves that teachers use to guide students' thinking toward more expert understanding of the problem space. This study highlights the importance of the thinking processes that students engage in as they participate in technology‐mediated PBL and the accompanying teacher attention to student thinking through supporting pedagogical moves. Practitioner Notes What is already known about this topic Technology‐mediated problem‐based learning (PBL) can invite an immersive experience for learners to engage with authentic problems. Broad framing for effective PBL includes features such as structured group work, a tutorial process for structuring knowledge and action plans, constructive investigation, and cognitive mentorship. The results on PBL have been mixed depending upon how it is enacted. It typically takes very skilled teachers and additional inherent structure. What this paper adds It demonstrates that novice‐expert shifts are possible in high school students' reasoning about technology‐supported, medical‐based problem solving. It reveals six nuanced thinking scaffolds that teachers used to support students' shift toward the more expert conceptions. It identifies seven thinking moves that students engaged in during the problem‐solving context. Implications for practice and/or policy It alerts practitioners to the need to attend to the pedagogical moves that they employ to support student thinking. It demonstrates the importance of the thinking processes that students engage in as they participate in technology‐mediated PBL. It demonstrates that successful learning in technology‐mediated PBL contexts is accompanied by teacher attention to student thinking and supporting pedagogical maneuvers.